Increased Passive Ankle Stiffness and Reduced Dorsiflexion Range of Motion in Individuals With Diabetes Mellitus - Rao, Smita R. (2006)
BACKGROUND: The purpose of our study was to compare ankle range of motion and stiffness in individuals with and without diabetes mellitus using a reliable and valid technique and to document the effect of knee flexion and severity of pathology on ankle range of motion and stiffness. METHODS: Twenty-five individuals with diabetes mellitus and 64 nondiabetic individuals, similar in age and gender profile, participated in this study. RESULTS: Results revealed that individuals with diabetes mellitus had both significantly lower peak dorsiflexion range of motion (5.1 and 11.5 degrees, p < 0.001) and higher passive ankle stiffness (0.016 and 0.008 Nm/kg/degree, p < 0.01) than non-diabetic individuals. In individuals with diabetes mellitus, a positive relationship between glycemic control and duration of diabetes mellitus and ankle stiffness ((r(2) = 0.48 and 0.24 respectively, p < 0.01 for both) was found. CONCLUSION: While decreased range of motion and increased stiffness in the diabetes mellitus population seem clinically intuitive, as far as we know this is the first study to confirm the concurrent existence of both these findings in the plantarflexors in individuals with diabetes mellitus. We applied a reliable and valid technique, one that allowed control of confounding factors such as knee flexion position and differences in determination of end range of motion, and documented a mean 41% loss in dorsiflexion excursion. Changes in the muscle, stemming from underlying pathology, are hypothesized to account for a significant part of the lost range of motion. Changes in ankle range of motion and stiffness may have important implications in plantar loading and ulcer formation.